Parasite Contamination of Water Source at Pangkalan Masyhur Sub-district, Medan Johor District - Sunna Vyatra Hutagalung; Rahmah Khairuna Damanik; Pongruj Rattaprasert (Sumatera Medical Journal, 2024)
Background: Water utilization by humans and animals can generate biological pollutants which may contaminate the water. These contaminants come from waste products that may contain bacteria, protozoa, and other parasites. Objective:  The aims of this study was to determine the contamination of water source by pathogens, particularly parasites at Medan, North Sumatera, Indonesia. Methods: This was a descriptive study with cross sectional design and simple random sampling. Results: We found Paramecium caudatum from nine samples (8,7%) collected from the open wells and the nearby river streams, followed by hookworm larva in one tap water sample (1%). Conclusion: No protozoa such as Entamoeba spp., Cryptosporidium spp., and Giardia spp. found in any of the samples. Based on this data, the abundant presence of P.caudatum represented the condition of high organic debris in the open wells and the nearby river streams. Additionally, the presence of hookworm larva in the tap water indicated the distribution system was contaminated with the surrounding soil.